Edukasi Penanganan Limbah Obat dan Limbah B3 Di Kelompok PKK Gonggangan, Bolon, Colomadu, Karanganyar - Fauzi, Ahmad; Saifudin, Azis; Hidayatullah, Muhammad Haqqi; Ramadhan, Muhammad Reza; Kholifatul Hakimah, Wafiq; Mufidah Maulina, Fariha (Universitas Muhammadiyah Surakarta, 2024)
The management of hazardous and toxic waste (B3) and household pharmaceutical waste is a critical issue due to its adverse effects on human health and the environment. B3 waste, such as used batteries, light bulbs, spent oil, and aerosol cans, poses a significant risk of contaminating soil, water, and air if not properly managed. Pharmaceutical waste, including expired or damaged medications, also has the potential to harm public health. Improper disposal can lead to pollution, causing acute health problems such as neurological damage and respiratory disorders, as well as long-term risks such as cancer and genetic mutations. To address this issue, an community program was conducted for the community in Dusun Gonggangan, Bolon, Colomadu, Karanganyar, involving the local women's community group (PKK). The method employed consisted of education through presentations and interactive Q&A sessions. The materials covered waste identification, segregation, storage, and disposal according to proper waste management standards. Interactive discussions encouraged active community participation to understand and adopt responsible household waste management practices. The results showed an increase in community awareness regarding the proper management of B3 and household pharmaceutical waste. The implementation of appropriate waste management practices is expected to mitigate the negative impacts of waste on health and the environment. Thus, effective waste management contributes to improved public health and supports environmental sustainability and ecosystem preservation.